Tetanus: A public health problem in Brazil despite prevention strategies and measures (Research, Society and Development, 2021)
Objective: To describe the epidemiological profile of reported cases of accidental Tetanus in Brazil between the years 2009 and 2019. Methodology: This is a quantitative descriptive study, with data obtained in the DataSUS platform, through the following strategy: “Health Information (TABNET)”, in the group “Diseases and Diseases of Notifications - 2007 onwards (SINAN)”, with emphasis on “tetanus”. The following variables were applied: regions of Brazil, year of notification (2009 to 2019), age, sex, education, and evolution. Results: The research findings reveal that the male sex represents 85.3% of the cases of accidental Tetanus and that the Northeast region presents the highest percentage of notifications (33.2%). Of those contaminated, 38.1% deceased. Individuals aged between 20 and 59 years represent 60.2% of the total cases and those who have not completed studies from the 1st to the 4th grade of elementary school represent 28.9%. 2011 is the year with the most confirmed cases of accidental tetanus (335). Conclusion: The results indicate that, even with the drop in the number of cases, accidental Tetanus is still a public health problem and has a high lethality rate. Therefore, there is an urgent need to keep the vaccination schedule up to date and expand the knowledge of Brazilians about ways of preventing the disease.